Digital transformation and global society : second International Conference, DTGS 2017, St. Petersburg, Russia, June 21-23, 2017, Revised selected papers /: second International Conference, DTGS 2017, St. Petersburg, Russia, June 21-23, 2017, Revised selected papers. (2017) - Unknown
No abstract available